Early Post-Vaccination Gene Signatures Correlate With the Magnitude and Function of Vaccine-Induced HIV Envelope-Specific Plasma Antibodies in Infant Rhesus Macaques - Vijayan, K. K. Vidya; Cross, Kaitlyn A.; Curtis, Alan D.; Van Rompay, Koen K. A.; Pollara, Justin; Fox, Christopher B.; Tomai, Mark; Hanke, Tomáš; Fouda, Genevieve; Hudgens, Michael G.; Permar, Sallie R.; De Paris, Kristina (Frontiers in Immunology, 2022)
A better understanding of the impact of early innate immune responses after vaccine priming on vaccine-elicited adaptive immune responses could inform rational design for effective HIV vaccines. The current study compared the whole blood molecular immune signatures of a 3M-052-SE adjuvanted HIV Env protein vaccine to a regimen combining the adjuvanted Env protein with simultaneous administration of a modified Vaccinia Ankara vector expressing HIV Env in infant rhesus macaques at days 0, 1, and 3 post vaccine prime. Both vaccines induced a rapid, but transient, systemic innate response, evident by elevated inflammatory plasma cytokines and altered gene expression. We identified 31 differentially-expressed genes (DEG) with increased mRNA levels on day 1 compared to day 0 in the HIV protein vaccine group. In contrast, in the group that received both the Env protein and the MVA-Env vaccine a single, downregulated, DEG was identified, implying that the MVA-Env modified the innate response to the adjuvanted protein vaccine. The DEG represented immune pathways associated with complement activation, type I interferon and interleukin signaling, pathogen sensing, and induction of adaptive immunity. DEG expression on day 1 was correlated to Env-specific plasma IgG levels at week 14 and with Env-specific antibody-dependent cytotoxicity responses at week 34. A protein-protein interaction network confirmed that several of the DEG-encoded proteins have predicted interaction partners that are important for B cell activation. These results support the idea that vaccine-induced HIV-specific antibody responses can be optimized through the modulation of the innate response to the vaccine prime.